Faktor – Faktor Yang Mempengaruhi Profitabilitas Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2014-2018 - Ayu Nur Aprilya; Diana Dwi Astuti; Lia Rachmawati (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2020)
This study aims to determine the influence of Sales Growth, Firm Size, Value Added Capital Employee (VACA), Value Added Human Capital (VAHU), and Structures Capital Value Added (STVA) on Profitability in Manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2014 - 2018. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2014 to 2018. The sampling technique in this study used purposive sampling. The sample in this study were 60 companies from 184 manufacturing companies listed on the Indonesia Stock Exchange (BEI). The data analysis technique used is multiple linear regression analysis. The results of this study indicate that there is a simultaneous influence on Sales Growth, Firm Size, Value Added Capital Employee (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA) on Profitability in Manufacturing companies for the period 2014-2018. Based on the partial test of Firm Size and VAHU variables has a significant effect on profitability. While the Sales Growth variable VACA, and STVA showed that the results have no and significant effect on profitability.